Associations of arsenic metabolites, methylation capacity, and skin lesions caused by chronic exposure to high arsenic in tube well water. Issue 1 (23rd October 2015) - Yang, Linsheng; Chai, Yuanqing; Yu, Jiangping; Wei, Binggan; Xia, Yajuan; Wu, Kegong; Gao, Jianwei; Guo, Zhiwei; Cui, Na
ABSTRACT: To investigate the interaction between skin lesion status and arsenic methylation profiles, the concentrations and proportions of arsenic metabolites in urine and arsenic methylation capacities of study subjects were determined. The results showed that the mean urinary concentrations of iAs (inorganic arsenic), MMA (monomethylarsonic acid), DMA (dimethylarsinic acid), and TAs (total arsenic) were 75.65, 68.78, 265.81, and 410.24 μg/L, respectively, in the skin lesions subjects. The highest values were observed in the multiple skin lesions subjects. Higher %iAs and %MMA, and lower %DMA, PMI (primary methylation index), and SMI (secondary methylation index) were found in skin lesions subjects. The multiple skin lesions subjects had highest %iAs and %MMA, and lowest %DMA, PMI, and SMI. The prevalence of skin lesions strongly, positively correlated with arsenic levels in drinking water. The elder persons also had higher frequency of skin lesions compared with younger persons. It can be concluded that arsenic levels in drinking water significantly affected the prevalence of skin lesions. Male subjects usually had higher proportions of skin lesions when compared with female subjects. Moreover, it may be concluded that MMA was significantly related to single skin lesion, whereas DMA and iAs were associated with multiple skin lesions. It seemed that MMA had greater toxicity to hyperkeratosis, whereas DMA and iAs had higher toxicity to depigmentation or pigmentation. © 2015 Wiley Periodicals, Inc. Environ Toxicol 32: 28–36, 2017.